Use of Primary Health Care Service in Cardiovascular Patients Admitted to Hospital - Kübra Sultan Dengiz; Deniz Koçoğlu Tanyer (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study was to determine the use of primary health care services in individuals diagnosed with cardiovascular diseases and to investigate the relationship between health status and sociodemographic characteristics and health/disease characteristics. METHODS: The sample of this descriptive study consisted of 313 individuals with cardiovascular disease aged twenty years and over who were admitted to a hospital for any reason by haphazard sampling method. A questionnaire was used to collect the data. RESULTS: The mean age of the participants was 59.21 +- 13.52 years. It was seen that 46% of the individuals had hypertensive disease and 88.5% of them had continuous medication. The rate of those who prefer family health care center as the first institution for cardiovascular diseases is 13.4%, and the rate of those who prefer family health care center, as the first institution in case of any health problem is 20.1%. The individuals 89.1% came to the hospital without referral from the family health care center, 16.9% of them found family health care centers inadequate. DISCUSSION AND CONCLUSION: It is seen that cardiovascular patients who apply to the hospital benefit less from primary health care services. Strengthening the management of cardiovascular patients in primary care is the main suggestion of this study.